MENINGKATKAN PEMAHAMAN KONSEP MATA PELAJARAN MATEMATIKA PADA MATERI TAKSIRAN KASAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PESERTA DIDIK KELAS IV SD NEGERI KARUNDANG 1 - Wahyuni, Jayanti Dwi; Yulianto, Fazri (LPPM Universitas Bina Bangsa, 2024)
This research aims to improve the understanding of the concept of rough estimation material in mathematics subjects in grade 4 SD Negeri Karundang 1 by using the problem-based learning (PBL) model. The problem of understanding mathematical concepts is a major challenge in the learning process in elementary schools. This research applies PBL as a learning method that focuses on real problem solving, collaboration, and concept oriented with the hope of improving students understanding of concepts. This research uses classroom action research as its research method. The collection of data was conducted through concept understanding tests before and after the application of the PBL model, as well as observations to monitor student involvement in the learning process. The results showed that understanding concepts of students increased significantly after the application of the PBL model. Students participated more actively in learning, collaborated with peers, and were able to connect math concepts with real life situations. The findings support the effectiveness of the PBL model in improving students understanding of mathematical concepts, especially in rough estimation material. The implication of this research is that problem based learning can be a good alternative method to improve students concept understanding at the primary level. Teachers should consider using this method in teaching for better learning outcomes